Pengaruh Kepercayaan Anggota, Kualitas Pelayanan, Kualitas Produk Dan Mobile Banking Terhadap Kepuasaan Anggota: Studi Kasus Pada KSPPS BMT Mitra Umat - Eka Putriana; Ali Imron (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
the formulation of the problems in this study are (1) How is the Effect of Member Trust on Member Satisfaction at KSPPS BMT Mitra Umat? (2) How is the Effect of Service Quality on Member Satisfaction at KSPPS BMT Mitra Umat? (3) How is the Effect of Product Quality on Member Satisfaction at KSPPS BMT Mitra Umat? (4) How is the Effect of Mobile Banking Use on Member Satisfaction at KSPPS BMT Mitra Umat? (5) How is the Effect of Member Trust, Service Quality, Product Quality, and Use of Mobile Banking on Member Satisfaction at KSPPS BMT Mitra Umat Pekalongan?. This research is quantitative. The object of this research is members of KSPPS BMT Mitra Umat in Pekalongan. This research uses purposive sampling technique, the data collection technique is a questionnaire, and the sample of this research is 100 respondents. After conducting the research, the researcher obtained data calculated using the Slovin formula. SPSS was used to analyze the data. The data analysis technique used is multiple linear regression equation analysis, T test, F test, and coefficient of determination analysis. The results of this study are Member Trust, Service Quality, Product Quality, and Use of Mobile Banking partially and simultaneously affect Member Satisfaction KSPPS BMT Mitra Umat.